1999
DOI: 10.1111/j.1745-4522.1999.tb00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Lipids of Indian Mackerel to Gamma Irradiation

Abstract: The effect of gamma irradiation (1.5 and 2 kGy) on the lipids of Indian mackerel (Rastrelliger kanagurta) stored at 0–2C was studied. No major differences in lipid composition of fish was observed as a result of irradiation and subsequent storage for up to 14 days. However, higher carbony I values in irradiated samples during the initial storage of fish was revealed. Irradiation also had no adverse effect on the nutritionally important omega‐3 polyunsaturated fatty acids (PUFA) of the fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Similar observations have been reported by Lakshmanan et al (1999), who observed higher myristic and palmitic acids values and lower stearic acid values with higher irradiation doses in studies on lipid stability in irradiated Indian mackerel. Palmitoleic (C16:1), oleic (18:1), and linoleic (C18:2) acids were higher (p < 0.05) in shrimp irradiated with 6 kGy compared to non-irradiated shrimp (Table 1).…”
Section: Analysis Of Irradiated Shrimpsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar observations have been reported by Lakshmanan et al (1999), who observed higher myristic and palmitic acids values and lower stearic acid values with higher irradiation doses in studies on lipid stability in irradiated Indian mackerel. Palmitoleic (C16:1), oleic (18:1), and linoleic (C18:2) acids were higher (p < 0.05) in shrimp irradiated with 6 kGy compared to non-irradiated shrimp (Table 1).…”
Section: Analysis Of Irradiated Shrimpsupporting
confidence: 90%
“…Since fish lipids are more unsaturated as compared to those of red meat, their sensitivity to irradiation is one of the parameters that has been considered to optimize radiation doses used for fish preservation (LAKSHMANAN et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst, this fraction increased in 1 kGy irradiated sample for the same period. Accordingly, PUFA in seafood are highly susceptible to gamma ionisation and the presence of oxygen increases lipid oxidation rate (Lakshmanan et al. , 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Lakshmanan, Venugopal, Rao, and Bongirwar (1999) found that doses of 1.5 and 2 kGy had no adverse effects on the n-3 PUFA of Indian mackerel stored for 14 days at 0-2 C. However, Al-Kahtani et al (1996) observed that in the case of Spanish mackerel, irradiation with doses of between 1.5 and 10 kGy caused a decrease in some fatty acids (16:0 and 16:1) and an increase in others (18:0 and 18:1). These changes, detected immediately after irradiation, were not consistent with those occurring during storage at 2 AE 2 C for 20 days.…”
Section: Effect Of Gamma Irradiation On H and G Portion Stored At à18 Cmentioning
confidence: 93%